The Efektifitas Konsentrasi Pembuatan Handsanitizer Dari Ekstrak Daun Mengkudu (Morinda Citrifolia L.) Bentuk Gel Dalam Menghambat Pertumbuhan Staphylococcus Aureus - R. Bara, Libernia Permata (Jurnal Sains dan Teknologi Laboratorium Medik, 2024)
Health is very important for life, one way to maintain a healthy body is by washing your hands using a hand sanitizer to kill bacteria. The aim of the research was to determine the effectiveness of hand sanitizer concentration from noni leaf extract (Morinda Citrifolia L.) in inhibiting the growth of Staphylococcus aureus. Staphylococcus aureus bacteria can cause skin and soft tissue infections such as pneumonia, osteomyelitis, and endocarditis. Natural hand sanitizer made from the Noni Plant (Morinda Citrifolia L.) contains alkaloids, flavonoids, saponins, tannins, which are antibacterial. The composition of the hand sanitizer is carbomer, TEA (triethanolamine), alcohol and glycerin. Research Method (Total Plate Count), count colonies on Mueller Hinton Agar media. The results of the research (Handsanitizer concentration 15%) grew colonies with an average number of (74 x 108 CFU/ml), (Handsanitizer concentration 20%) with an average number (73.54 x 108 CFU/ml). (Hand sanitizer concentration 25%) average amount (56.8 x 108 CFU/ml). (Handsanitizer concentration 30%) average amount (46.7 x 108 CFU/ml), (Handsanitizer concentration 35%) average amount (42.5 x 108 CFU/ml). Data analysis showed that based on the Anova test, the results showed that there was an influence of megkudu leaf extract hand sanitizer on the growth of Staphylococcus aureus. In the post hoc test, it was found that hand sanitizer with a concentration of 35% was the best concentration in inhibiting bacterial growth.